Analysis of the Convergence Communication Model on Waste Bank Program Stakeholders in South Tangerang City, Indonesia - Mirza Shahreza; Sarwititi Sarwoprasodjo; Hadi Susilo Arifin; Dwi Retno Hapsari (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2020)
This research aims to analyze a convergent communication model that supports the sustainability of the waste Bank community in South Tangerang City. The type of research conducted is qualitative descriptive research. Data obtained through observation and in-depth interview. The results illustrate that the convergence communication model in the waste bank program has three supporting stakeholders carrying three interests, that is, who sees the theme of the environment as a source (ruler), objects (city government/ Environmental office) and Spirit (waste bank Community) that finally formed a converged communication, namely the equality of delivery and acceptance of the message so that it becomes mutual understanding, and interdependence that positions the waste Bank as a public space in discussing environmental themes, especially waste management problems. Keywords: environmental communication, convergent communication, stakeholders, waste bankABSTRAK Penelitian ini bertujuan untuk menganalisis sebuah model komunikasi konvergen yang mendukung keberlanjutan komunitas Bank sampah di kota Tangerang Selatan. Jenis penelitian yang dilakukan adalah Penelitian deskriptif kualitatif. Data diperoleh melalui pengamatan, dan wawancara mendalam. Hasil penelitian menggambarkan bahwa model komunikasi konvergensi pada program Bank sampah terdapat tiga pemangku kepentingan pendukungnya membawa tiga kepentingan, yaitu, yang melihat tema lingkungan sebagai sumber (penguasa), objek (pemerintah/ Dinas Lingkungan Hidup Tangerang Selatan) dan spirit (komunitas Bank sampah) yang akhirnya membentuk komunikasi konvergen, yaitu kesetaraan penyampaian dan penerimaan pesan sehingga menjadi saling pengertian, serta saling ketergantungan yang memposisikan Bank sampah sebagai ruang publik dalam membahas tema lingkungan, terutama masalah pengelolaan sampah. Kata Kunci: komunikasi lingkungan, komunikasi konvergensi, pemangku kepentingan, bank sampah